Aptamer conjugated silver nanoparticles for the colorimetric detection of arsenic ions using response surface methodology. Issue 11 (7th June 2015) - Divsar, Faten; Habibzadeh, Kazhal; Shariati, Shahab; Shahriarinour, Mahdi
<x xml:space="preserve">Abstract</x> Aptamer conjugated silver nanoparticles were synthesized for the colorimetric detection of As(iii) ions in solution. A central composite design combined with response surface methodology was employed to maximize the efficiency of sensing.